Sticky cost behavior of bank’s executive compensation in four South East Asian countries - Slamet Sugiri; Rahmat Febrianto; Etik Kresnawati (Journal of Economics, Business, and Accountancy Ventura, 2016)
Some studies indicate that selling, general, and administrative (SG&A) cost have sticky characteristics. A cost is sticky if it increases as the activity increases, but it does not decrease as the activity decreases, in the same proportion as it increases. Different from previous studies that focus solely on SG&A costs in, mostly, manufacturing companies, we specifically focus on specific cost and specific industry. In this case, we focus on compensation costs in banks from four South East Asian countries. We choose banks’ executive compensations since banks in South East Asia have been publicly reporting their compensation. Executive compensation itself is a component of SG&A, so it may have sticky characteristic with it. We apply bootstrap method to tackle small sample problem in every country. Results show that executive compensations are not sticky, but, on the contrary, anti-sticky since the compensation decreases faster when the revenue decreases than its increases when the revenue increases. This finding gives a new perspective on the characteristics of executive compensation expenses as a part of SG&A cost.